2020
DOI: 10.3389/fgene.2020.00796
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of Alternative Splicing Signature Reveals Prognostic Predictor for Esophageal Carcinoma

Abstract: Background: Alternative splicing (AS) is a molecular event that drives protein diversity through the generation of multiple mRNA isoforms. Growing evidence demonstrates that dysregulation of AS is associated with tumorigenesis. However, an integrated analysis in identifying the AS biomarkers attributed to esophageal carcinoma (ESCA) is largely unexplored. Methods: AS percent-splice-in (PSI) data were obtained from the TCGA SpliceSeq database. Univariate and multivariate Cox regression analysis was successively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…A recent study revealed that human METTL2A and METTL2B form a complex with the DALRD3 (DALR anticodon binding domain containing 3) protein to recognize particular arginine tRNAs 41 . To date, METTL26 has been sparsely studied; its substrate remains unknown and current reports of METTL26 only discuss it in terms of exon skip alternative splicing in cancer 42 45 . Our pathway analysis of METTL26-associated proteins in CPTAC and CCLE datasets indicated that METTL26 might be involved in the vacuolar transport in human cancer (Data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that human METTL2A and METTL2B form a complex with the DALRD3 (DALR anticodon binding domain containing 3) protein to recognize particular arginine tRNAs 41 . To date, METTL26 has been sparsely studied; its substrate remains unknown and current reports of METTL26 only discuss it in terms of exon skip alternative splicing in cancer 42 45 . Our pathway analysis of METTL26-associated proteins in CPTAC and CCLE datasets indicated that METTL26 might be involved in the vacuolar transport in human cancer (Data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…More and more AS-related prognostic models have been established, showing excellent efficacy in various cancers. Researcher have used splicing changes to construct predictive models for different types of tumors, such as hepatocellular carcinoma, glioblastoma, cervical cancer, sarcoma, and esophageal carcinoma [36][37][38][39][40]. Interestingly, AML has been identified to share some common prognostic markers of AS with other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of splicing alterations in esophageal carcinoma identified 2389 AS events that occurred in esophageal cancer and were related to patient outcomes. 172 Another study characterized the predictive power of different splicing events with esophageal cancer patient outcomes. It was found that 83% of alternative acceptor site splicing events could be associated with patient survival, 99% of alternative donor site events and 97% of alternative terminator site events.…”
Section: Targeting Alternative Splicing For the Development Of Therapeutic Targets And Biomarkersmentioning
confidence: 99%